Assessment of Response to Phototherapy in Neonatal Jaundice in a Tertiary Care Hospital in West Bengal, India - Mukherjee, Samarpita; Sur, Arindam; Mandal, Sandip Kumar; Chakraborty, Indranil (International Journal of Human and Health Sciences (IJHHS), 2026)
Most of the neonates suffer from unconjugated hyperbilirubinemia due to rapid destruction of fetal haemoglobin. This condition is successfully treated by phototherapy. A descriptive, cross-sectional study was conducted in the Department of Biochemistry, College of Medicine and Sagore Dutta Hospital, West Bengal, India, in collaboration with Department of Pediatrics, to compare unconjugated bilirubin versus total bilirubin in neonates over the course of treatment and to determine which one is best prognostic marker in phototherapy. Blood samples were collected from 148 neonates with jaundice undergoing phototherapy for unconjugated hyperbilirubinemia on commencement of phototherapy i.e., 3rd and 5th, 7th days of commencement of phototherapy and their unconjugated bilirubin, conjugated bilirubin and total bilirubin were measured using micro slide technology on Vitros 250 Dry Chemistry analyzer. All the neonates were thoroughly clinically evaluated to monitor the prognosis of phototherapy. Over the days, mean values of unconjugated bilirubin of the 1st, 2nd and 3rd samples of neonates showed a significant decrease (p<0.001), when baby undergoes successful phototherapy; however, the total bilirubin showed no significant change (p>0.05). In case of delta bilirubin, we did not find any statistically significant findings in any within group or between group comparisons (p>0.05). International Journal of Human and Health Sciences Vol. 10 No. 02 Apr’26 Page: 92-98